The Effect of Polymorphisms in the CYP2D6 and CYP2C9 Genes on the Clinical Efficacy of Tramadol and Ketorolac When Using the Accelerated Recovery Protocol in Patients With Uncomplicated Acute Calculous Cholecystitis Who Underwent Cholecystectomy - A. A. Muradyan; D. A. Blagovestnov; D. A. Sychev; P. A. Yartsev; M. L. Rogal; L. N. Kerimova; V. T. Koroshvili; I. A. Yepifanova (Неотложная медицинская помощь)
Relevance. One of the key components of the accelerated recovery protocols (ARP), in addition to minimizing the surgical approach, is an adequate postoperative analgesia. Despite this, applied postoperative analgesia combinations are not devoid of drawbacks, such as lack of effective postoperative analgesia and the presence of side effect. The use of a pharmacogenetic approach to analgesic therapy for the purpose of its personalization may increase the effectiveness and safety of the use of analgesics. In particular, the presence of an inactive CYP2D6*4 allele , in which the conversion of tramadol to its active metabolite is reduced, contributes to the insufficient efficacy of the drug. As for non-steroidal anti-inflammatory drugs, the presence of CYP2C9*2/*3 polymorphisms leads to a decrease in drug metabolism and a longer half-life, resulting in the increase of the clinical effect and the risk of adverse reactions. Thus, genotyping of patients with the determination of the presence of specific genetic factors can rationalize the postoperative analgesia.Aim of study. Evaluation of the possible association of polymorphisms of the CYP2D6 and CYP2C9 genes with the clinical efficacy of tramadol and ketorolac in relation to postoperative pain.Material and methods. This observational clinical study involved 107 patients with uncomplicated acute calculous cholecystitis who underwent videolaparoscopic cholecystectomy and perioperative treatment according to ARP. All patients underwent whole blood sampling followed by real-time polymerase chain reaction genotyping. Analgesic efficacy was assessed using a visual analog scale (VAS) and McGill Pain Questionnaire.Results. In CYP2D64* carriers pain was higher than that of wild-type carriers, according to VAS and McGill Pain Questionnaire in all investigated periods. In carriers of CYP2C9*2, the pain syndrome was lower than in carriers of the wild type at all intervals studied. In carriers of CYP2C9*3 pain was lower only after 2 and 6 hours, also according to McGill Pain Questionnaire.Conclusion. 1. The presence of the polymorphic marker CYP2D6*4 may reduce the efficacy of postoperative tramadol analgesia compared with wild type. 2. The presence of the polymorphic marker CYP2C9*2 and CYP2C9*3 may increase the efficacy of ketorolac pain relief compared to wild type.